如何用正弦定理证明余弦定理 如何用余弦定理证明正弦定理

1个回答

  • 第一个问题:

    ∵A+B=180°-C,

    ∴sinC=sin(A+B)=sinAcosB+cosAsinB,-cosC=cos(A+B).

    ∴(sinC)^2

    =(sinAcosB)^2+2sinAcosBcosAsinB+(cosAsinB)^2

    =(sinA)^2[1-(sinB)^2]+[1-(sinA)^2](sinB)^2+2sinAcosBcosAsinB

    =(sinA)^2-(sinAsinB)^2+(sinB)^2-(sinAsinB)^2+2sinAcosBcosAsinB

    =(sinA)^2+2sinAsinB(cosAcosB-sinAsinB)+(sinB)^2

    =(sinA)^2+(sinB)^2+2sinAsinBcos(A+B)

    =(sinA)^2+(sinB)^2-2sinAsinBcosC.

    ∴(2RsinC)^2=(2RsinA)^2+(2RsinB)^2=2(2RsinA)(2RsinB)cosC.

    由正弦定理,有:a/sinA=b/sinB=c/sinC=2R,∴a=2RsinA、b=2RsinB、c=2RsinC,

    ∴c^2=a^2+b^2-2abcosC.

    同理可证:a^2=b^2+c^2-2bccosA、b^2=a^2+c^2-2accosB.

    第二个问题:

    ∵a^2=b^2+c^2-2bccosA、b^2=a^2+c^2-2accosB,两式相减,得:

    a^2-b^2=b^2-a^2-2bccosA+2accosB,∴2(a^2-b^2)=2c(acosB-bcosA),

    ∴c=(a^2-b^2)/(acosB-bcosA),

    ∴a^2

    =b^2+[(a^2-b^2)/(acosB-bcosA)]^2

    -2b[(a^2-b^2)/(acosB-bcosA)]cosA,

    ∴(a^2-b^2)(acosB-bcosA)^2=(a^2-b^2)^2

    -2b(a^2-b^2)(acosB-bcosA)cosA,

    ∴a=b,或(acosB-bcosA)^2=a^2-b^2-2b(acosB-bcosA)cosA.

    一、当a=b时,自然有:a/sinA=b/sinB.

    二、当(acosB-bcosA)^2=a^2-b^2-2b(acosB-bcosA)cosA时,得:

    (acosB)^2+(bcosA)^2-2abcosAcosB=a^2-b^2-2abcosAcosB+2(bcosA)^2,

    ∴a^2[1-(cosB)^2]=b^2[1-(cosA)^2],

    ∴(asinB)^2=(bsinA)^2,∴asinB=bsinA,∴a/sinA=b/sinB.

    综合一、二,得:a/sinA=b/sinB.同理可证:a/sinA=c/sinC.

    ∴a/sinA=b/sinB=c/sinC.